Inskripsi pada Makam Kiai Hasan Maulani: Sosok Pejuang Islam dari Kuningan - Syarifuddin Syarifuddin (Jurnal Lektur Keagamaan, 2014)
Epigraphy is the study of inscriptions as a data source in the study of history. The inscription on an ancient tomb is part of a study of epigraphy. Tomb Kiai Hasan Maulani have inscriptions that can be studied through Archaeo-Epigraphy approach. Administratively, this tomb is in the Tomb Complex Mojo Kiai, Wuloan Village, North Tondano District, not far from Kampung Jawa in Tondano, Minahasa. The inscription and the Arabic language that serves as a description of Kiai Hasan Maulani, as well as proof of the greatness of Islam in the era. Remembrance sentence contained in the inscription proves that Hasan Maulani is expert remembrance. He is renowned as a scholar adherent Syattariah congregation. The congregation strongly recommends tradition to remember the God at anytime. Kiai Hasan is also known as a national hero. He is a fighter and defender of the rights of the people are seized by the Dutch colonial.Keywords: inscription, zikr, tomb